The Form of The Bajo Tribe’s House as an Adaptation Process Residential Environment - Mulyati, Ahda; Najib, Muhammad; Astha, A.M. Yamin (Green Publisher Indonesia, 2024)
The Bajo tribe is a tribe that lives on the coast or islands. This is related to their livelihood, namely fishermen. Even though most already occupy land, fishermen still choose land close to the beach. The research aims to discover the essential things in their lives as a process of adaptation to the residential environment. The method used is naturalistic qualitative research by selecting several samples of residential houses on land and those that still choose land above water as cases to be analyzed. Even though there have been changes in occupying residential land, the Bajo tribe still has several adjustments regarding the placement of their homes, which are incredibly close to water or the coast. Residential houses on coastal land still have a back room facing the sea as the main room and are shaped like a house on stilts, while the front faces the road as a space for social interaction. Residential houses that occupy land and highways are the primary orientation and areas for social interaction. Although there is still a back room, it is not the main room. The shape of the building has changed both in structure and building materials. Almost all buildings on the land are permanent, consisting of several rooms, functioning as a bedroom, living room, etc.. In contrast, houses that occupy water land still use wood, bamboo, and woven sago leaf roofs and only have a onebedroom family room equipped with a back terrace.